PELANGGARAN ETIKA BISNIS - Qomariyah, Nurul (Magister Manajemen Universitas Wisnuwardhana, 2018)
Violations of business ethics that occur at this time, become a problem in itself. One of the factors supporting the occurrence of these violations is due to lack of basic knowledge about business ethics and the freedom of business people in carrying out economic activities, as a result many business people are competing in improving market mechanisms, Business should be assessed from a moral standpoint, just like all other human activities also seen from a moral standpoint. Because when not looking at the moral aspect of doing business, business people only think about how to increase sales turnover, and not only increase turnover, but also do things that are not ethical, such as: bribery, corruption, collusion and nepotism, it makes people uneasy . Adverse effects that will occur if a company is immoral and enforces the norms that apply in business ethics then it can have an impact on consumers' distrust of their products and can complicate business development again. Key words : Violation, Bussines ethic, case